Australian Education and Rural-regional Sustainability - Green, Bill (Australian and International Journal of Rural Education, 2015)
This paper seeks to develop a case for (re)thinking education and sustainability with specific reference to rural Australia. It proposes a critical view of rural-regional sustainability, taking into account notions of bioregionality and ecosocial change. Two key points are made. One is the assertion that rural education as such is better reformulated as education for rural-regional sustainability. The other is the introduction of a reconceptualised view of public education, as explicitly embracing formal, informal and non-formal sectors, and considering schools therefore within a larger, more comprehensive view of educational practice addressed to the task of educating the public. Education thus understood is a crucial resource for developing informed, active citizenship and community regeneration in the Anthropocene age.